Viajeras / Paloma Castaęda - Castaęda Ceballos, Paloma (Legado de la historia ; 41)
Bibliografía: p. 197-206 | Contiene los viajes de Flora Tristán, Emilia Serrano García (Baronesa de Wilson), Emilia Pardo Bazán, Sofía Casanova, Carmen de Burgos (Colombine) y María Lejárraga